Edward Brown papers - Brown, Edward, 1771-1844.
Correspondence, journals, and financial and legal papers primarily relating to shipping and shipbuilding in Newburyport, Mass., and Thomaston, Me., Newburyport and vicinity in the War of 1812, local church events, and family affairs. Family correspondence includes letters from Brown's brothers who were ship captains and merchants in Newburyport, and letters of a cousin, Samuel Tenney, containing observations on the War of 1812 and genealogical sketches of the Brown and allied families.
Tradesman.
Collection material in English.
Keywords: Tenney, Samuel, -- 1748-1816 -- Correspondence; Brown family; Newburyport (Mass.) -- Church history; Merchants -- Massachusetts -- Newburyport; Ship captains -- Massachusetts -- Newburyport; Shipbuilding -- Maine -- Thomaston; Shipbuilding -- Massachusetts -- Newburyport; Shipping -- Maine -- Thomaston; Shipping -- Massachusetts -- Newburyport; Massachusetts -- History -- War of 1812.; Massachusetts -- Social life and customs; Tradesmen